Factors Associated with Non-Recovery of Renal Function in Patients with Septic Acute Kidney Injury - Suttiruk, Pongpon; Chuasuwan, Anan (Journal of the Nephrology Society of Thailand, 2024)
Background: Acute kidney injury (AKI) is a common complication in patients with infection and septicemia, contributing to increased mortality and longer hospital stays. However, factors predicting renal recovery in patients with septic AKI remain unclear. This study investigated biochemical factors associated with renal recovery in septic AKI patients. Methods: This was a retrospective, single-center study of patients admitted with infection-associated AKI between January 1st, 2015, and December 31st, 2020. Patients were categorized into full recovery and non-recovery groups, and factors associated with non-recovery of renal function within 90 days were analyzed. Results: A total of 4,431 patients with septic AKI were included in the final analysis. Of these, 2,429 patients (54.82%) were in the full recovery group, and 2,002 patients (45.18%) were in the non-recovery group. Independent predictors of non-recovery included older age, male gender, AKI severity, the need for dialysis and assisted ventilation, thrombocytopenia, elevated serum phosphorus and magnesium levels, and lower serum albumin. There was no association between underlying conditions or the degree of chronic kidney disease and renal outcomes. Conclusions: Older age, male gender, infection and AKI severity, the need for dialysis, thrombocytopenia, and lower serum albumin were associated with non-recovery of renal function in patients with septic AKI.